THYROIDITIS SUBACUTA FROM EPSTEIN BARR VIRUS- CASE REPORT - Ivana Mladenovska Stojkoska; Aleksandra Stevcevska; Iskra Bitoska; Irfan Ahmeti (My University, 2022)
Introduction: Subacute thyroiditis (SAT) is a self-limiting inflammation of the thyroid gland that is associated with a three-phase clinical course of hyperthyroidism, hypothyroidism and euthyroidism. Case report: A 23-year-old woman presented at otorinolafingologist with stuffy nose, sore throat and pain on the anterior neck. She was treated with antibiotic and corticosteroid inhalation therapy. After 2 weeks, the codition deteriorated with increased body temperature 37,8 oC ,appearance of malaise, loss of appetite and intensifion of the pain in the throat that spread to the upper part of the neck and ears. She was referred to an internist. А miss diagnosis of primary hyperthyroidism was made and thiamazole therapy was prescribed. After one mount from the appearance of the first simptom, the patient came in our hospital. Results: ECG - sinus tachycardia 120 beats/min. From the laboratory: suppressed TSH 0.004 mU/l and elevation of: fT4-59 pmol/l fT3-14 pmol/l, thyroglobulin-280, sedimentation- 80, CRP-30mg/l. Thyroid ultrasound: diffusely enhanced, hypoechoic, non-homogeneous with vaguely demarcated margins and absent vascularization.Thyroid scan: empty in addition to de-Quarvain thyroiditis. Positive serology for Epstein Barr virus. Our patient was treated with NSAIDs, b blockers, corticosteroids in a small dose (20 mg), advice for fluid intake and rest. Discussion: Differential diagnosis can often lead to another etiology of thyreotoxicоsis, but good anamnesis and accurate investigations lead to correct diagnosis and appoprionate treatment. Conculusion: SAT resolves spontaneously in 90-95% of cases. In some patients, analgesic therapy with NSAIDs or corticosteroids in small doses is required in order to reduce pain and symptoms of thyrotoxicosis.